Natural killer cells: development, diversity and applications to human disease - Caligiuri, Mike (Henry Stewart Talks, 2009)
Human NK cell development, What factors are responsible for NK cell development?, How does KL or FL assist IL-15 in NK cell development?, NK progenitor, NK precursor, mature NK cell, Only CD34dimCD45RA(+) HPC differentiate into CD56bright NK cells, NK cells are in human lymph nodes and are CD56bright, Putative stages of human NK cell differentiation in nodes/tonsils, How NK cell development fits in human lymphopoiesis, IL-15 and human NK cell survival, Adoptive transfer of NK cells into IL-15-deficient mice, IL-15 transgene, Lymphoblastic leukemia, Human NK cell subsets, Do NK cell subsets have unique immunoregulatory roles?, LPS activation, NK cell-derived IFN-γ in the innate immune response, Innate immunoregulator, CD56bright, Innate cytotoxic effector, CD56dim, How do inhibitory NKR work?, How does KIR work?, Haplo-mismatch BMT